Vitiligo pathogenesis: autoimmune disease, genetic defect, excessive reactive oxygen species, calcium imbalance, or what else? - Schallreuter, K; Bahadoran, P; Picardo, M; Slominski, A; Elassiuty, Y; Kemp, E; Giachino, C; Liu, J; Luiten, R; Lambe, T; Le Poole, I; Dammak, I; et al. (2008)
The pathobiology of vitiligo has been hotly disputed for as long as one remembers, and has been a magnet for endless speculation. Evidently, the different schools of thought--ranging, e.g. from the concept that vitiligo essentially is a free-radical disorder to that of vitiligo being a primary autoimmune disease--imply very different consequences for the best therapeutic strategies that one should adopt. As a more effective therapy for this common, often disfiguring pigmentary disorder is direly needed, we must strive harder to settle the pathogenesis debate definitively--on the basis of sound experimental evidence, rather than by a war of dogmatic theories. Recognizing, however, that it is theories which tend to guide our experimental designs and choice of study parameters, the various pathogenesis theories on the market deserve to be critically, yet unemotionally re-evaluated. This Controversies feature invites you to do so, and to ask yourself: is there something important or worthwhile exploring in other pathogenesis scenarios than those already favoured by you that may help you improve your own study design, next time you have a fresh look at vitiligo? Vitiligo provides a superb model for the study of many fundamental problems in skin biology and pathology. Therefore, even if it later turns out that, as far as your own vitiligo pathogenesis concept is concerned, you have barked-up the wrong tree most of the time, chances are that you shall anyway have generated priceless new insights into skin function along the way.